Enhancing global maritime education: a qualitative exploration of post-internship perspectives and preparedness among cadets - Simanjuntak, Marudut Bernadtua; Rafli, Zainal; Utami, Sintowati Rini (Intelektual Pustaka Media Utama, 2024)
This research investigates the post-internship phase for cadets at the Sekolah Tinggi Ilmu Pelayaran Jakarta with a focus on curriculum effectiveness, vocational training impact, language proficiency challenges, technology integration preferences, and the intricate influence of geographical diversity. Results reveal the integrative curriculum's success in transitioning theoretical knowledge to practical application, emphasizing the critical role of vocational training. Language proficiency nuances and a desire for balanced technology integration emerge, while geographical diversity affects cultural adaptation. Implications include refining maritime education, fostering inclusivity, and aligning educational practices with industry demands. Recognizing limitations, the study advocates for broader institutional research and targeted language proficiency investigations in future studies.